The effect on 4-month judo training period on anaerobic capacity, blood lactate changes during the post Wingate test recovery, and resting plasma cortisol, and testosterone levels in male senior judokas - Obminski, Z.; Ladyga, M.; Borkowski, L.; Wisniewska, K. (Journal of Combat Sports and Martial Arts, 2013)
Wingate test is a standardized laboratory effort, which is commonly used for examination of anaerobic capacity. The biomechanical parameters of work and power recorded during the test is combined frequently with blood lactate (LA) determination throughout post- test recovery. The objectives of this experiment was to examine an effect of 4-month training period on anaerobic capacity and LA response to the effort. Material and methods. Eight Polish senior judokas were enrolled to the study. The examination was carried out twice, the fist one after 1-month detraining period (January) and the second after 4-month training, prior to main competition (May). In both terms resting plasma cortisol ( C) and testosterone (T) were determined, capillary blood was sampled for determination of lactate over post-Wingate (30s) passive recovery as follows: +1, +3, +5, +7, +9, +11 and +30 minutes. Biomechanical parameters were recorded on- line during the efforts. Results. The training resulted a little, non significant (by 7%) improvement of biomechanical features. In both trials the shape of curve representing LA time course was almost the same and there were no term-related differences separately for each of the seven time points LA. However, when the aggregated data, i.e concurrently the all LA observations (2 terms*56 measurements), were taken into calculation, difference between two terms was significantly (p<0.02), lower in May. Mean T level was significantly higher in May. Conclusions. In conclusion (i) the training period elicited an increase of contribution of aerobic energetic processes during Wingate test, (ii) aggregated results from multiple LA measurements gave better information about post-exercise lactic acidosis.